Catalytic dehydrocoupling of methylamine borane using Yamashita's [Ir(PBP)] boryl complex – characterisation of a novel highly fluxional Ir tetrahydride. (10th November 2022) - Decker, David; Drexler, Hans-Joachim; Baumann, Wolfgang; Reiß, Fabian; Beweries, Torsten
Abstract : Catalytic dehydropolymerisation of methylamine borane using the boryl pincer complex [(PBP)Ir(H)(Cl)]/NaO t Bu proceeds via an unusual highly fluxional Ir tetrahydride. Abstract : We report the synthesis and characterisation of two iridium pincer monocarbonyl complexes possessing Yamashita's PBP boryl ligand. Both complexes can be prepared by reaction of the parent hydride chloride complex (1 ) with base in the presence of CO. Complex 1 as well as the 18-electron complex [(PBP)Ir(CO)(H)2 ] (2 ) were tested as precatalysts for the catalytic dehydrocoupling of amine boranes, showing that only 1 selectively produces polyaminoboranes. A tetrahydride complex 4 was identified as the resting state of catalysis and characterised in solution and the solid state. Combination of NMR spectroscopy, X-ray analysis and DFT computation suggest the presence of a highly fluxional hydride environment with only one of the hydride ligands bridging the Ir centre and the boryl unit.